Α7 Nicotinic acetylcholine receptor gene and reduced risk of Alzheimer's disease. Issue 4 (5th December 2007) - Carson, R; Craig, D; McGuinness, B; Johnston, J A; O'Neill, F A; Passmore, A P; Ritchie, C W
Abstract : Background: Sporadic Alzheimer's disease (AD) is a common disabling disease of complex aetiology for which there are limited therapeutic options. We sought to investigate the role of the α7 nicotinic acetylcholine receptor gene ( CHRNA7 ) in influencing risk of AD in a large population. CHRNA7 is a strong candidate gene for AD for several reasons: (1) its expression is altered differentially in the AD brain; (2) it interacts directly with β amyloid peptide (Aβ42 ); and (3) agonist activation induces several neuroprotective pathways. Methods: In this study we used a genetic haplotype approach to assess the contribution of common variation at the CHRNA7 locus to risk of AD. Fourteen single nucleotide polymorphisms (SNPs) were genotyped in 764 AD patients and 314 controls. Results: Three blocks of high linkage disequilibrium (LD) and low haplotype diversity were identified. The block 1 TCC haplotype was significantly associated with reduced odds of AD (p = 0.001) and was independent of apolipoprotein E (APOE) status. Individual SNPs were not associated with risk for AD. Conclusions: We conclude that genetic variation in CHRNA7 influences susceptibility to AD. These results provide support for the development of α7nAChR agonists or modulators as potential drug treatments for AD. Further work is necessary to replicate the findings in other populations.